Laugier–Hunziker syndrome: A case report - Zigu S. Krishn; Yogesh Devaraj; Mukunda Ranga Swaroop; Rashmi Rameshchandra Mallya; Neethu Nag; Kadari Yashwanth Reddy (Pigment International)
Laugier–Hunziker syndrome (LHS) is a rare, benign pigmentary disorder characterized by unique pigmentation over mucosa, nails, and acral sites, arising spontaneously during adulthood. It has no malignant potential or systemic involvement. It has a female preponderance (2:1 ratio). The pigmentary lesions in LHS respond poorly to therapy, and has high recurrence. Since LHS is a diagnosis based on exclusion, we discuss the differential diagnosis of mucocutaneous hyperpigmentation. We present a case of a 66-year-old man with LHS.